High hydrostatic pressure, pulsed electric fields and cold plasma in the food production chain: Principles and industrial applicability (Research, Society and Development, 2021)
The search for non-thermal technologies has been gaining space in the market due to changes in consumers' eating habits and concern for preserving the environment. This technology is highly advantageous for the microbial decontamination of food products, including sporulates and pathogenic microorganisms. In this context, this review aimed at a systematic study of the literature on the main non-thermal technologies, using the databases of Science Direct and Web of Science, with the keyword “non-thermal technologies”. The selected articles were submitted for analysis using the Vosviewer software. After interpreting the density maps obtained in the software, it was noticed that the most studied non-thermal technologies, in the last five years (2015-2020), were the technologies of high hydrostatic pressure, pulsed electric field and cold plasma. The main highlights of the technologies were (i) reduction of the microbial load in the food, the cellular structure being an important factor in the inactivation of microorganisms, as well as (ii) the need for more sustainable industrial applications, demanding new technologies in the market.